The Impact of Central Bank Policy Mix on Banking Risk Behavior - Wijaya, Miryam B Lilian; Wibisana, Gema Adi; Utama, Chandra (Signifikan: Jurnal Ilmu Ekonomi, 2025)
Research Originality: The study investigates the impact of a coordinated policy mix on Banking Risk Behavior in creating credit.Research Objectives: This research aims to determine the effect of the policy mix on lending and the role of risk behavior in Indonesia.Research Methods: We use the Structural Vector Autoregression (SVAR) estimation technique for data 2012Q1-2021Q3.Empirical Results: The study found that monetary policy does not affect credit directly through credit interest rates. Monetary policy affects credit indirectly through its ability to influence an internal variable of banks and strengthen it through interaction with macroprudential policies. The study found that deposit and capital determine the amount of credit disbursed. The study results found that the policy mix of monetary and macroprudential policies effectively influenced recognition in Indonesia. Mixed policies reinforce one another.Implications: To manage bank risk behavior in distributing credit, a mix of monetary and macroprudential policies is needed. When coordinated, both policies reinforce each other and are more effective than when done separately.JEL Classification: E52, E580, E510How to Cite:Wijaya, M. B. L., Wibisana, G. A. & Utama, C. (2025). The Impact of Central Bank Policy Mix on Banking Risk Behavior. Signifikan: Jurnal Ilmu Ekonomi, 14(1), 1-16. https://doi.org/10.15408/sjie.v14i1.41334